2024
DOI: 10.3390/healthcare12030333
|View full text |Cite|
|
Sign up to set email alerts
|

The Value of the COVID-19 Yorkshire Rehabilitation Scale in the Assessment of Post-COVID among Residents of Long-Term Care Facilities

Łukasz Goździewicz,
Sławomir Tobis,
Michał Chojnicki
et al.

Abstract: The COVID-19 Yorkshire Rehabilitation Scale (C19-YRS) is a patient-reported outcome measure designed to assess the long-term effects of COVID-19. The scale was validated and is commonly used in the general population. In this study, we assess the utility of the C19-YRS in evaluating the post-COVID burden among residents of long-term care facilities with a mean age of 79. C19-YRS and Barthel index evaluations were performed among 144 residents of long-term care facilities reporting new or worsened symptoms or f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The C19-YRS (COVID-19 Yorkshire Rehabilitation Scale) was the literature's first published and validated PROM for LC [7], and it has been recommended by both NICE and NHS England [8]. The scale has been used in several LC studies which have indicated support for the content and construct validity, as well as the responsiveness of the scale to reliably capture persistent symptoms [9][10][11][12]. C19-YRS gives scores in three domains: symptom severity (SS), functional disability (FD), and overall health (OH).…”
Section: Introductionmentioning
confidence: 99%
“…The C19-YRS (COVID-19 Yorkshire Rehabilitation Scale) was the literature's first published and validated PROM for LC [7], and it has been recommended by both NICE and NHS England [8]. The scale has been used in several LC studies which have indicated support for the content and construct validity, as well as the responsiveness of the scale to reliably capture persistent symptoms [9][10][11][12]. C19-YRS gives scores in three domains: symptom severity (SS), functional disability (FD), and overall health (OH).…”
Section: Introductionmentioning
confidence: 99%